Optimizing collegiate female soccer athlete technical and physical performance through position-specific conditioning training - Nguyen, M. N.Q.; Fry, A. C.; Garver, M. J.; Eserhaut, D. A.; Yang, Y.; Crawford, D. A. (The Journal of Strength and Conditioning Research, 2025)
osition-specific conditioning training (PSCT), which addresses the distinct physical and technical demands of soccer positions, has emerged as a promising training methodology. The aim of this study was to examine the effects of PSCT on the physical and technical performance of collegiate female soccer players. Eighteen National Collegiate Athletic Association (NCAA) Division II female soccer athletes (height = 169 ± 5.2 cm; body mass = 64.3 ± 7.2 kg; age = 20.1 ± 0.9 years) participated in a controlled, two-phase, two-group crossover study spanning 5 weeks of training per phase. Performance assessment included the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT1), sprint speed, repeated sprint ability, Agility T-test, and Loughborough Soccer Passing Test (LSPT) under nonfatigue and fatigued conditions. Training load (TL) was monitored using the session rating of perceived exertion (sRPE). The design of the PSCT program encompassed 4 high-intensity drills for attackers and defenders. Each drill targeted an intensity of 90-95% heart rate maximum for 4-minute work bouts, interspersed with 4-minute active recovery periods. Normal conditioning methods served as the control. Postintervention, significant improvements were observed in the YYIRT1 endurance test for both groups (µ = 22.75%, p < 0.05). However, a significant improvement was observed only in the PSCT group for LSPT under nonfatigued and fatigued conditions (µ = 13.1%, p < 0.05 and µ = 15.5%, p < 0.05, respectively). PSCT showed no significant impact on sRPE or other physical performance metrics. The study confirmed that PSCT is an effective conditioning modality for enhancing skills and endurance without increasing the TL for NCAA female soccer athletes, fostering a well-rounded approach to player development.